2013
DOI: 10.1021/om400493k
|View full text |Cite
|
Sign up to set email alerts
|

Di- and Trinuclear Ruthenium-, Rhodium-, and Iridium-Functionalized Pyridyl Aromatic Ethers: A New Class of Antiparasitic Agents

Abstract: Two new di-and tripyridyl aromatic ether ligands (1 and 2) have been synthesized using the Williamson ether method. Functionalization of these ligands with either dichlorido(p-cymene)ruthenium(II), dichlorido(pentamethylcyclopentadienyl)rhodium-(III), or dichlorido(pentamethylcyclopentadienyl)iridium(III) fragments yielded three di-and three trinuclear organometallic complexes (1a−c and 2a−c). Both ligands act as monodentate donors to each metal center via the pyridyl nitrogen atoms, and this coordination mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 87 publications
1
29
0
Order By: Relevance
“…[4,24,36] It is possible that complexes 1 and 8 may be active at concentrations > 20 mm.T here are few published accounts where Rh III and Ir III analogues of Ru II complexes werea lso tested for antiplasmodiala ctivity in the same study. [15,17,37,38] In mosto ft hese reported studies, the type of ligand used contained different pharmacophores com- [a] Half-lives (t 1/2 )a nd pseudo-first order rate constantsw ith standard error in parentheses. pared to 1-14 and furthermore their intracellular targets are likely to be different, which may account for why the ruthenium sulfadoxinyl complexes 1 and 8 are not active.…”
Section: In Vitro Biological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…[4,24,36] It is possible that complexes 1 and 8 may be active at concentrations > 20 mm.T here are few published accounts where Rh III and Ir III analogues of Ru II complexes werea lso tested for antiplasmodiala ctivity in the same study. [15,17,37,38] In mosto ft hese reported studies, the type of ligand used contained different pharmacophores com- [a] Half-lives (t 1/2 )a nd pseudo-first order rate constantsw ith standard error in parentheses. pared to 1-14 and furthermore their intracellular targets are likely to be different, which may account for why the ruthenium sulfadoxinyl complexes 1 and 8 are not active.…”
Section: In Vitro Biological Activitymentioning
confidence: 99%
“…In the last decade, the study of metallo-therapeuticsa sp otentiala ntiparasitics has gainedm omentum. [15][16][17][18][19][20] In particular, the discoveryo ft he potent activity of ferroquine, [21][22][23] af errocene-chloroquine conjugate, has encouraged the design of novel metal complexes containing validated drugs caffolds. [4,24] Sulfadoxine is ad rug belonging to the class known as sulfonamidesa nd is usedi nc ombination with pyrimethamine ( Figure 1A)t ot reat malaria caused by the P. falciparum parasite.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, reports revealed that Ru complexation improves the antiplasmodial activity in comparison to free ligands e.g. Ru-pyridyl ester (Chellan et al, 2014) or ether complexes (Chellan et al, 2013), Ru-lapachol complexes (Barbosa et al, 2014) and Ru-cotrimazole complex (Iniguez et al, 2016). Conversely, the substitution of Fe by Ru in ferroquine derivatives can increase the antiplasmodial activity against the K1 resistance strain (Beagley et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[(η 6 ‐ p ‐cymene)Ru II (PTA)Cl 2 ] (RAPTA‐C), have exhibited activity against metastases . Moreover, ruthenium–arene complexes incorporating steroidal, picolinamide or carbohydrate ligands have demonstrated promising pharmacological activities particularly antiproliferative effects, making them viable candidates for further biological study.…”
Section: Introductionmentioning
confidence: 99%